Implications of built and social environments on the academic success among African American youth: testing Strong African American Families intervention effects on parental academic racial socialization - Murry, Velma McBride; Gonzalez, Catherine M.; Debreaux, Marlena L.; Coates, Erica E.; Berkel, Cady (Frontiers in Psychology, 2023)
Studies exploring widening academic disparities have highlighted the role of racialized school settings, which have given way to incidents of discrimination and unfair treatment for students of color, disproportionately affecting African American youth. Research also shows that familybased preventive interventions may avert negative outcomes for this population through the promotion of protective socialization practices. Consequently, the current study tests the efficacy of a culturally tailored preventive family-based program to foster induced changes in academic promotive parenting practices that prepare youth to advance academically by navigating negative race-related experiences in school settings. Data collected over four time periods from the Strong African American Families (SAAF) efficacy trial (Murry & Brody, 2004) with 667 African American families in rural Georgia were used for this study. Structural equation modeling analyses demonstrated that the SAAF program was associated with positive intervention induced changes in parental academic race-related socialization, which in turn, was indirectly associated with reduced school compromising behaviors through the enhancement of racial pride. While discrimination compromised academic success, our findings highlight the protective nature of racial pride in dissuading academic failure and school dropout through the promotion of academic success. This study confirms that a family-based prevention program holds promise to address academic disparities through the enhancement of parenting and youth protective processes that buffer youth from succumbing to racialized social environments such as schools. Implications for research, educational policy, and preventive interventions are discussed.